Bottlenecks in the Transferability of Antibiotic Resistance from Natural Ecosystems to Human Bacterial Pathogens - Martinez, Jose L. (Frontiers in Microbiology, 2012)
It is generally accepted that resistance genes acquired by human pathogens through horizontal gene transfer originated in environmental, non-pathogenic bacteria. As a consequence, there is increasing concern on the roles that natural, non-clinical ecosystems, may play in the evolution of resistance. Recent studies have shown that the variability of determinants that can provide antibiotic resistance on their expression in a heterologous host is much larger than what is actually found in human pathogens, which implies the existence of bottlenecks modulating the transfer, spread, and stability of antibiotic resistance genes. In this review, the role that different factors such as founder effects, ecological connectivity, fitness costs, or second-order selection may have on the establishment of a specific resistance determinant in a population of bacterial pathogens is analyzed.